A noble-metal-free MoS2 nanosheet-coupled MAPbI3 photocatalyst for efficient and stable visible-light-driven hydrogen evolution. Issue 22 (19th February 2020) - Wang, Fang; Liu, Xiangyu; Zhang, Zhengguo; Min, Shixiong
Abstract : MoS2 nanosheets (MoS2 NSs) as a cocatalyst in situ coupled with MAPbI3 lead to a superior composite photocatalyst for visible light H2 evolution from HI splitting. Abstract : We report that MoS2 nanosheets (MoS2 NSs) as a cocatalyst in situ coupled with MAPbI3 lead to a highly efficient composite photocatalyst for visible-light-driven photocatalytic H2 evolution. The most efficient MAPbI3 /MoS2 NSs composite exhibits a high H2 evolution rate (206.1 μmol h −1 ) in MAPbI3 -saturated HI solution, which is 121 times higher than that of pristine MAPbI3 (1.7 μmol h −1 ) and greatly superior to that of MAPbI3 /Pt/C (68.5 μmol h −1 ), and the composite is very stable for H2 evolution in a 156 h reaction.